Exploring the interpersonal relationships and marketing practices among women entrepreneurs: Phenomenological approach / Carolina Sandra Giang - Giang, Carolina Sandra (2019)
The emergence of women entrepreneurship in Small Medium Enterprises (SMEs) had achieved recognition as a major player in bringing innovativeness and utilizing their capabilities towards achieving SMEs development goals in Malaysia. Entrepreneurs of SMEs have the inclination to utilize interpersonal relationships in business transactions especially in the aspect of the marketing activities. An interpersonal relationship is a skill widely regarded as an intangible asset possessed by women due to the lack of tangible resources and empirical studies have shown the interpersonal relationship is an important element in marketing practices. Therefore, the purpose of this study is to explore the interpersonal relationships and marketing practices of women entrepreneurs through the extraction of entrepreneurial experiences. This study adopts qualitative phenomenological method using in-depth interviews to extract and identify the common meaning of interpersonal relationships and marketing practices of the lived experiences of 22 women entrepreneurs domiciled in Sarawak, Malaysia. The data was organized, transcribed, retrieved and coded using Atlas.ti7 software while the analysis and the interpretation of the data conducted manually to achieve greater precision and consistency in the resulting concepts and theory development. The main findings of the dissertation identify six main themes and sub-categorized into fourteen sub-themes. These six main themes include women entrepreneurs' express meaning of interpersonal relationships; interpersonal relationship practices of women entrepreneurs; personalized, relational, fast and immediate marketing approach; selectiveness in the choice of traditional promotional tools; interpersonal relationships capabilities of the women entrepreneurs; and social entrepreneurial orientation of the women entrepreneurs. Further, the dissertation develops an integrated 6Ps Model of Women Entrepreneurs Practices based on the six main themes that become the main theoretical contribution to this dissertation. Interestingly, the unexpected findings of this dissertation explain that religion interweaved with the way women operates their business. Hence, the integration of religion and business, altruistic behaviors and community engagement are a result of the values held by the women entrepreneurs in this dissertation.